SPIRITUAL JOURNEY IN SAIVA SIDDHANTA - Arulsamy, S. (1986)
Saivism is one of the three major religious faithsl that have moulded the thought and life of the Hindus in India. Its distinctive feature is the exaltation of Siva as supreme God and the worship of him. But Šaivism itself is not a single cult; it covers many faiths with nuances according to belief and religious experiences. They are based on the nucleus of twenty-eight Agamas and they also accept the authority of the Vedas. In addition to the Vedas and the Agamas, each one of them added its own literature in the language of the region where it flourished. Of these éaiva faiths, Siva Siddhãnta is an important one, and it is known as the Šaivism of Tamilnadu.
Keywords: SAIVA SIDDHANTA